Advances in evolutionary developmental biology - Streelman, J. Todd (Jeffrey Todd) (Hoboken, New Jersey : Wiley-Blackwell, 2014)
Providing outstanding breadth of coverage in evo-devo, Advances in Evolutionary Developmental Biology provides a comprehensive review of the milestones of research in evolution and development and outlines the exciting research agenda for the field going forward. Compiling the viewpoints of a diverse group of field experts, this timely text expands the now-mature science of evo-devo into more complex areas of research. This essential reference is destined to become the go-to source for ideas and hypotheses for a new generation of graduate students in evolutionary and developmental biolo.
Microfluidic Advances for Developmental and Behavioral Studies in C. elegansMicrofluidic Culture Systems for Studying Genetic and Environmental Effects on D. rerio Development; Mammalian Embryonic Development in Microsystems; Conclusion; References; 5: From Black and White to Shades of Gray: Unifying Evo-Devo through the Integration of Molecular and Quantitative Approaches; Introduction; The Geometry of Development: A Quantitative Approach; A Brief Review of GMs; How GM Can Be Used to Study the Evolution of Development.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Evolutionary developmental biology; SCIENCE -- Life Sciences -- Anatomy & Physiology; Evolutionary developmental biology; Developmental biology; Embryos; Evolution (Biology); Electronic books; Electronic books